Vitamins and Neural Tube Defects - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The use of vitamin supplements by women around the time of conception was examined and compared in those having babies with neural tube defects, those with still births or some other type of malformation, and in women who had normal babies.